Susceptibility of HIV-1 to Tipranavir and Other Antiretroviral Agents in Treatment-Experienced Patients: The UTILIZE Study - D. Baxter, John; Bhatti, Laveeza; Coakley, Eoin; Bartczak, Jennifer; McDonough, Marita; Vinisko, Richard; J. Piliero, Peter (Current HIV Research, 2010)
Objectives: The primary objective was to assess HIV-1 susceptibility to the protease inhibitor (PI) tipranavir and other antiretroviral (ARV) agents among treatment-experienced patients (TEP). Secondarily, clinicians' use of resistance testing was examined. Methods: UTILIZE was an observational study conducted at 40 sites in the United States. Patients currently failing a PI-based regimen were randomized to receive either a genotype (GT) or combined phenotype-genotype test (PGT) and a treatment decision was made at the second study visit. Results: 246 patients enrolled, 236 had resistance test results, and 139 (59%) had evidence of HIV-1 resistance to ≥1 PI. Among these 139 patients, more than 50% had viruses that remained sensitive to tipranavir and darunavir, whereas susceptibility to other PIs was markedly lower (<22%). Increasing prior PI exposure was associated with reduced susceptibility to most ARV agents. After obtaining resistance test results, 83% of patients changed therapy. Newly available or investigational ARVs were used frequently. The reason investigators most often cited for changing therapy was the patient resistance test results (82%) and the most common reason for not changing therapy was the inability to construct an active regimen. The majority of patients who exhibited PI resistance received two or more active agents in the new regimen. Conclusions: Overall, 59% of TEPs failing a PI-based regimen had HIV-1 with PI resistance. The majority of these patients' viruses remained sensitive to either tipranavir or darunavir. Investigators used results from resistance assays to construct a new regimen, frequently with newer agents. In PI-experienced patients, tipranavir and darunavir remain the most likely available active PIs.
Keywords: Genotypic susceptibility